Aux/IAA and ARF Gene Families in Salix suchowensis: Identification, Evolution, and Dynamic Transcriptome Profiling During the Plant Growth Process - Wei, Suyun; Chen, Yingnan; Hou, Jing; Yang, Yonghua; Yin, Tongming (Frontiers in Plant Science, 2021)
The phytohormone auxin plays a pivotal role in the regulation of plant growth and development, including vascular differentiation and tree growth. The auxin/indole-3-acetic acid (Aux/IAA) and auxin response transcription factor (ARF) genes are key components of plant auxin signaling. To gain more insights on regulation and functional features of Aux/IAA and ARF genes during these processes, we identified 38 AUX/IAA and 34 ARF genes in the genome of Salix Suchowensis, and characterized the gene structures, conserved domains and amino acids compositions. Phylogenetic analysis from some typical land plants showed that the Aux/IAA and ARF genes in Salicaceae origined from common ancestor and significantly amplified by the eudicots ancestral hexaploidization and the “salicoid” duplication before the divergence of poplar and willow occurred. By analyzing the dynamic transcriptome profilings, some Aux/IAA and ARF genes were detected to be involved in the regulation of plant growth, especially in the plant initial growth process. Meanwhile, we found that several miR160/miR167-ARFs expressions were in agreement with canonical miRNA-ARF interactions, suggesting miRNAs were possibly involved in the regulation of auxin signaling pathway and plant growth process. Overall, this study comprehensively analyzed sequence features, origin and expansion of Aux/IAA and ARF genes, and provided useful information for further studies on the functional involvement of auxin signaling genes in plant growth process.